An Overview of the Emergence and Challenges of Land Reclamation: Issues and Prospect - Kingsley Eghonghon Ukhurebor; Uyiosa Osagie Aigbe; Robert Birundu Onyancha; Juliana Ngozi Ndunagu; Otolorin Adelaja Osibote; Joseph Onyeka Emegha; Vincent Aizebeoje Balogun; Heri Septya Kusuma; Handoko Darmokoesoemo (Applied and Environmental Soil Science)
The issues of land degradation are directly or indirectly influenced by human and/or natural actions, and it is one of the most challenging issues confronting several regions of the world, especially developing nations. Notwithstanding the importance of land, its degradation consequences, possibly as a result of the various biological, physical, and chemical processes caused by some activities (both natural and man-induced) that diminish viable yield, result in a long-term, enduring devaluation of land. Hence, this present review study is dedicated to some of the most emerging and challenging issues in monitoring, rehabilitation, prevention, and management of land (land reclamation) drawn from existing publications. Also, the description of some of the most extreme procedures of land reclamation in some natural environments with distinct consideration to their positive features is discussed. Some illustrations and instances of the emergence and challenging issues in land reclamation and nature protection, as well as the possibilities and prospects of their resolutions, are discussed and presented.